Life expectancy, schooling, and lifetime labor supply: Theory and evidence revisited - Matteo Cervellati; Uwe Sunde (Institute for the Study of Labor (IZA), 2013)
This paper presents a theoretical and empirical analysis of the role of life expectancy for optimal schooling and lifetime labor supply. The results of a simple prototype Ben-Porath model with age-specific survival rates show that an increase in lifetime labor supply is not a necessary, nor a sufficient, condition for greater life expectancy to increase optimal schooling. The observed increase in survival rates during working ages that follows from the rectangularization of the survival function is crucial for schooling and labor supply. The empirical results suggest that the relative benefits of schooling have been increasing across cohorts of US men born 1840-1930. A simple quantitative analysis shows that a realistic shift in the survival function can lead to an increase in schooling and a reduction in lifetime labor hours.
Keywords: E20; J22; J24; J26; O11; 330; longevity; life expectancy; schooling; lifetime labor supply; rectangularization of the survival function